End-to-end Level-0 Data Simulation Tool for Future Spaceborne SAR Missions - Rodriguez-Cassola, Marc; Prats, Pau; Pinheiro, Muriel; Zonno, Mariantonietta; Nannini, Matteo; Sanjuan-Ferrer, Maria J.; Yagüe-Martinez, Nestor; Bordoni, Federica; Börner, Thomas; Krieger, Gerhard; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2018)
This paper presents the methodology for the end-to-end simulation of raw data of future spaceborne SAR systems, including monostatic, bistatic and multistatic, multichannel, wide-swath, very high resolution, or high-orbit systems. This methodology is expected to play a relevant role in the future to help in the validation of idealised performance models, the illustration of the impact of the different error sources from instrument, platform, or atmospheric propagation, the identification of requirement gaps, the refinement of acquisition strategies, and most prominently the tuning of processing and calibration algorithms. The paper also presents examples of two relevant systems of the next generation: the multi-channel, wide-swath Tandem-L system, and future bistatic and multistatic SAR missions.
Keywords: SAR; bistatic SAR; end-to-end simulation